Development and Validation of A Spectrofluorimetric Determination of Calf Thymus DNA Using a Terbium-Danofloxacin Probe - Naser Soltani; Jamshid Manzoori; Mohammad Amjadi; Farzaneh Lotfipour; Farzaneh Lotfipour (Tabriz University of Medical Sciences, 2016)
Background: Analysis of biomolecules is required in many biomedical research areas. A spectrofluorimetric method is proposed for determination of calf thymus DNA (ctDNA) based on the fluorescence enhancement of terbium-danofloxacin (Tb3+-Dano) in the presence of ctDNA. Methods: A probe with maximum excitation and emission wavelengths of 347 nm and 545 nm, respectively, was developed. The enhanced fluorescence intensity of Tb3+-Dano system was proportional to the concentration of ctDNA. The effective factors and the optimum conditions for the determination of ctDNA were studied. Under the optimum conditions of [Tris buffer]= 0.01 mol L-1 (pH 7.8), [ Tb3+]= 1×10-5 mol L-1 and [Dano]= 5×10-5 mol L-1, the maximum response was achieved. The developed method was evaluated in terms of accuracy, precision and limit of detection. Results: The linear concentration range for quantification of ctDNA was 36-3289 ng mL-1 and the detection limit (S/N=3) was 8 ng mL-1. The concentration of DNA extracted from Escherichia coli as an extracted sample was also determined using the developed probe. The concentration of DNA in extracted sample was determined using UV assay and developed method, the results were satisfactory. Conclusion: The proposed method is a simple, practical and relatively interference free method to follow up the concentrations of ctDNA.